2018
DOI: 10.1176/appi.ps.201700400
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis Literacy Among Latinos With First-Episode Psychosis and Their Caregivers

Abstract: Community campaigns and psychoeducation interventions within clinical settings are needed to improve psychosis literacy among Latinos with FEP. Increasing knowledge of psychosis and facilitating attributions of psychotic symptoms to serious mental illness have the potential to promote professional help seeking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
10
0
2
Order By: Relevance
“…A number of explanations have been considered for the prolonged DUP and treatment delay among white British and black Caribbean patients, including stigma, the tendency to seek help via GP, living with family which may help reduce burden of the illness and help manage symptoms [ 5 , 25 , 26 ]. However, a handful of studies have shown the role of family stigma in some ethnic groups on help-seeking delays for psychosis, and potentially leading to poor clinical and social functioning outcomes [ 27 , 28 ]. It has also been suggested that black African patients tend to experience acute onset of psychosis leading to more rapid presentation to services, which may explain the shorter DUP [ 21 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of explanations have been considered for the prolonged DUP and treatment delay among white British and black Caribbean patients, including stigma, the tendency to seek help via GP, living with family which may help reduce burden of the illness and help manage symptoms [ 5 , 25 , 26 ]. However, a handful of studies have shown the role of family stigma in some ethnic groups on help-seeking delays for psychosis, and potentially leading to poor clinical and social functioning outcomes [ 27 , 28 ]. It has also been suggested that black African patients tend to experience acute onset of psychosis leading to more rapid presentation to services, which may explain the shorter DUP [ 21 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Participant responses to open‐ended questions were coded by two independent raters. Coding guidelines were consistent with those used in previous studies (Calderon et al, 2015; López et al, 2018).…”
Section: Methodsmentioning
confidence: 60%
“…They were also more likely to correctly endorse the presence of a serious mental illness and less likely to attribute the hypothetical vignette's symptomatic behavior to merely being the result of life stressors. The observed increases in knowledge of psychosis are particularly important given that these predicted recommended professional help‐seeking in a prior study (López et al, 2018). Additionally, limited knowledge of psychosis contributes to the “cloud of uncertainty” that has been implicated in the pathways to care for first‐episode psychosis (Cabassa et al, 2018).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations